Inter-generational consequences for growing Caenorhabditis elegans in liquid - Lev, Itamar (2019)
In recent years, studies in Caenorhabditis elegans nematodes have shown that different stresses can generate multigenerational changes. Here, we show that worms that grow in liquid media, and also their plate-grown progeny, are different from worms whose ancestors were grown on plates. It has been suggested that C. elegans might encounter liquid environments in nature, although actual observations in the wild are few and far between. By contrast, in the laboratory, growing worms in liquid is commonplace, and often used as an alternative to growing worms on agar plates, to control the composition of the worms’ diet, to starve (and synchronize) worms or to grow large populations for biochemical assays. We found that plate-grown descendants of M9 liquid medium-grown worms were longer than control worms, and the heritable effects were already apparent very early in development. We tested for the involvement of different known epigenetic inheritance mechanisms, but could not find a single mutant in which these inter-generational effects are cancelled. While we found that growing in liquid always leads to inter-generational changes in the worms’ size, trans-generational effects were found to be variable, and in some cases, the effects were gone after one to two generations. These results demonstrate that standard cultivation conditions in early life can dramatically change the worms’ physiology in adulthood, and can also affect the next generations. This article is part of the theme issue ‘Developing differences: early-life effects and evolutionary medicine’.